Analisis Penggunaan Sistem Proporsional Tertutup Dalam Pesta Demokrasi 2024 - Loeky Kristanto; Tri Sosilowati (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Elections are very important in an effort to maintain the sovereignty of the people and democracy of the Indonesian state. A good election must pay attention to the system and the consequences of the system used. Indonesia is one of the countries that applies a proportional electoral system. The proportional system used by Indonesia since 1955 has two forms, namely a closed proportional system and an open proportional system. Indonesia currently uses an open proportional system after previously using a closed proportional system in 1998. However, in 2019 the open proportional system caused losses for Indonesia, ranging from money politics, a large budget spent by the government, to the loss of 527 lives of election organizers. This phenomenon has led researchers to examine the closed proportional system as a solution in the 2024 elections using normative research with a conceptual approach until researchers have the assumption that a closed proportional system by tightening the rules of the internal party system in the recruitment of people's representatives can be the answer to the weaknesses of the open operational system.